Intercropping Systems Modify Desert Plant-Associated Microbial Communities and Weaken Host Effects in a Hyper-Arid Desert - Zhang, Zhihao; Chai, Xutian; Tariq, Akash; Zeng, Fanjiang; Li, Xiangyi; Graciano, Corina (Frontiers in Microbiology, 2021)
Intercropping is an important practice in promoting plant diversity and productivity. Compared to the accumulated understanding of the legume/non-legume crop intercrops, very little is known about the effect of this practice when applied to native species on soil microbial communities in the desert ecosystem. Therefore, in the present study, bulk soil and rhizosphere microbial communities in the 2-year Alhagi sparsifolia (legume)/Karelinia caspica (non-legume) monoculture vs. intercropping systems were characterized under field conditions. Our result revealed that plant species identities caused a significant effect on microbial community composition in monocultures but not in intercropping systems. Monoculture weakened the rhizosphere effect on fungal richness. The composition of bacterial and fungal communities (β-diversity) was significantly modified by intercropping, while bacterial richness (Chao1) was comparable between the two planting patterns. Network analysis revealed that Actinobacteria, α- and γ-proteobacteria dominated bulk soil and rhizosphere microbial co-occurrence networks in each planting pattern. Intercropping systems induced a more complex rhizosphere microbial community and a more modular and stable bulk soil microbial network. Keystone taxa prevailed in intercropping systems and were Actinobacteria-dominated. Overall, planting patterns and soil compartments, not plant identities, differentiated root-associated microbiomes. Intercropping can modify the co-occurrence patterns of bulk soil and rhizosphere microorganisms in desert ecosystems. These findings provided a potential strategy for us to manipulate desert soil microbial communities and optimize desert species allocation in vegetation sustainability.